EFFECT OF HALAL LABELS, BRANDS, AND PRICES ON OVER THE COUNTER DRUGS PURCHASE DECISION IN WEST JAVA PROVINCE DURING COVID-19 - Ismail, Muhammad Iqbal; Sova, Maya; Limakrisna, Nandan (Dinasti International Journal of Management Science, 2022)
This study aims to determine whether the halal label, brand, and price variables affect consumers' decision to purchase over-the-counter drugs in the province of West Java during the covid-19 pandemic. The research sample amounted to 200 people. Sampling used a survey method with a data collection tool in the form of a questionnaire through a google form, measured using a Likert scale. The questionnaire was tested using validity and reliability tests. From the results of research with descriptive analysis, regression analysis prerequisite test, multiple linear regression test, and hypothesis testing using the SPSS version 25 program, it is known that there is a significant influence of independent variables halal label, brand, and price on the dependent variable purchasing decisions of over-the-counter drugs in West Java province during the covid-19 pandemic.